On becoming a leader - Bennis, Warren G. (Basic Books, 2009)
Management expert Bennis shows how individuals develop leadership traits and how organizations encourage or stifle potential leaders. The author profiles dynamic figures from diverse business arenas to demonstrate how all leaders share distinctive characteristics.